Identification of microfungi in Sg. Tekala and Sg. Langat sediments and their potential as copper and lead biosorption agents - Iskandar, Nur Liyana (2012)
Heavy metal pollution has received much attention as it is one of the world’s major environmental problems with negative impact on human and environment. The Department of Environment Malaysia (DOE) and US Environmental Agency (EPA) have classified heavy metal such as copper, lead, cadmium, arsenic and mercury as major pollutants in the environment. Their trace elements are discharged through numerous anthropogenic sources and collection into receiving systems such as sediment, soil and water. Researchers have developed several heavy metals removal technologies including chemical precipitation, ion exchange, reverse osmosis, electrodialysis and ultrafiltration. However, these technologies are becoming uneconomical and inefficient to remove heavy metals elements from industrial wastewaters. The need for new and more efficient and cost effective treatment method to remove heavy metal ions from wastewater have spurred research to replace the conventional methods. The use of fungi as agents of biosorption of heavy metal from contaminated sediments is an alternative that offer low cost biosorbent and nonharzardous biomaterial. In Malaysia, a study on the potential of microfungi obtained from Langat River and Tekala River as biosorption agent had not been attempted until this one. Therefore this present study was a pioneer study to determine the ability of microfungi from freshwater sediment to grow and remove Cu and Pb from liquid media. The potential fungal which can be used as biosorbent agent were also identified by using morphological characterization and their ITS sequences. In this study, a total of 89 isolates of microfungi were obtained from sediments of the Langat River and the Tekala River. Based on the Shannon Diversity Index, the Langat River (H´= 2.08) has higher microfungi diversity compared to the Tekala River (H´= 1.61). The isolates were identified and classified into 10 species namely Aspergillus niger, A. fumigatus, A. clavatus, Penicillium simplicissimum, P. janthinellum, P. purpurogenum, P. ochrochloron, P. aculeatum, P. pinophilum and Trichoderma asperellum by using morphological characterization and were futher characterized by using Internal Transcribed Spacer (ITS) sequences. Their tolerance and potential as biosorption agents of copper (Cu) and lead (Pb) were investigated and it was found that among these isolated microfungi, A. niger showed the highest tolerance to an uptake of Cu and Pb; followed by P. simplicissimum and T. asperellum. In the Cu toxicity test, among the 10 species of microfungi isolated, onlyA. niger and P. simplicissimum survived at 1000 mg/l of Cu concentration. While in the Pb toxicity test, only A. niger survived at 5000 mg/l concentration. The present study also determined that the maximum uptakes of Cu and Pb by A. niger were 200mg/l of Cu concentration (20.910 ± 0.581mg/g) and 250mg/g of Pb (54.046 ± 0.328mg/g). This study also suggested that A. niger, P. simplicissimum and T.asperellum could be biosorption agents of Cu and Pb with A. niger having the higher uptake.